Iraq Economic Monitor, Spring 2016 : Laboring through the Crisis - World Bank (World Bank, Washington, DC, 2016)
Iraq is facing daunting challenges of Islamic State of Iraq and Syria (ISIS) insurgency, political upheaval, and profound economic and humanitarian crises. Compounding the ISIS-related crisis, the sharp decline in global oil prices has resulted in significant decline in oil export revenues. Implementation of political reforms, announced in August 2015, has been slow due to constitutional constraints and systemic resistance to changes. Iraq’s economic prospects are subject to significant risks. Iraq has recently achieved some important steps towards strengthening its investment climate, but much remains to be done. An attractive investment climate is integral to economic growth and poverty reduction. A key task of the government is to balance the interests of society and individual firms. A stronger investment climate does not equate with a more comfortable life for individual firms. The government must manage these trade-offs: global analysis of the World Bank’s investment climate surveys shows that firms facing strong competition are on average fifty percent more likely to innovate than firms reporting no such pressure. Innovation, in turn, is a key ingredient for productivity improvement. The special focus section explores the different aspects of the investment climate in order to better understand their importance. With this background, the authors then look at Iraq’s investment climate and recent efforts to strengthen it. Finally, the authors look at priorities for improving Iraq’s investment climate going forward.